Hypothalamus volume and DNA methylation of stress axis genes in major depressive disorder: A CAN-BIND study report. (October 2021) - Suh, Jee Su; Fiori, Laura M.; Ali, Mohammad; Harkness, Kate L.; Ramonas, Milita; Minuzzi, Luciano; Hassel, Stefanie; Strother, Stephen C.; Zamyadi, Mojdeh; Arnott, Stephen R.; Farzan, Faranak; Foster, Jane A.; et al.
Abstract: Dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis is considered one of the mechanisms underlying the development of major depressive disorder (MDD), but the exact nature of this dysfunction is unknown. We investigated the relationship between hypothalamus volume (HV) and blood-derived DNA methylation in MDD. We obtained brain MRI, clinical and molecular data from 181 unmedicated MDD and 90 healthy control (HC) participants. MDD participants received a 16-week standardized antidepressant treatment protocol, as part of the first Canadian Biomarker Integration Network in Depression (CAN-BIND) study. We collected bilateral HV measures via manual segmentation by two independent raters. DNA methylation and RNA sequencing were performed for three key HPA axis-regulating genes coding for the corticotropin-binding protein ( CRHBP ), glucocorticoid receptor ( NR3C1 ) and FK506 binding protein 5 ( FKBP5 ). We used elastic net regression to perform variable selection and assess predictive ability of methylation variables on HV. Left HV was negatively associated with duration of current episode (ρ = −0.17, p = 0.035). We did not observe significant differences in HV between MDD and HC or any associations between HV and treatment response at weeks 8 or 16, overall depression severity, illness duration or childhood maltreatment. We also did not observe any differentially methylated CpG sites between MDD and HC groups. After assessing functionality by correlating methylation levels with RNA expression of the respective genes, we observed that the number of functionally relevant CpG sites differed between MDD and HC groups in FKBP5 (χ 2 = 77.25, p < 0.0001) and NR3C1 (χ 2 = 7.29, p = 0.007). Cross-referencing functionally relevant CpG sites to those that were highly ranked in predicting HV in elastic net modeling identified one site from FKBP5 (cg03591753) and one from NR3C1 (cg20728768) within the MDD group. Stronger associations between DNA methylation, gene expression and HV in MDD suggest a novel putative molecular pathway of stress-related sensitivity in depression. Future studies should consider utilizing the epigenome and ultra-high field MR data which would allow the investigation of HV sub-fields. Highlights: cg03591753, cg20728768 were highly predictive of hypothalamus volume in elastic net. Greater numssber of CpG sites correlated with RNA expression in MDD. Hypothalamus volume not found to be different between MDD and HC.